Vpliv kemijske sestave in toplotne obdelave na lastnosti feritnega nerjavnega jekla za magnetne ventile - Grešovnik, Ferdinand (Materiali in tehnologije, 2000)
In addition to the corrosion resistance and mechanical properties, the magnetic properties of the steels used for the closing elements of magnetic valves are the most important. Maximum permeability and minimum coercitivity are required. The latter is especially important in the case of magnetic valves controlled by an ac electric current. In the case of steel with 17% Cr and 0.4% Mo we have studied laboratory heats which must have the content of Si and Mn in the correct range to obtain the lowest coercitivity. The best method of annealing was determined in order to obtain a steep magnetization curve. It was established that the sequence of machining and heat treatment is very important. Resistance against intergranular corrosion was proved.
Keywords: jekla nerjavna; jekla feritna; obdelave toplotne; lastnosti magnetne; lastnosti mehanske; odpornost korozijska; nerjavna jekla; toplotna obdelava; magnetne lastnosti; mehanske lastnosti; korozijska odpornost